STATE AS AN INVESTOR AND CUSTOMER IN POSTGRADUATE EDUCATION: NATIONAL RESEARCH UNIVERSITIES NETWORK - Elena B. Mudrova; Elena B. Vinogradova (Moscow Polytechnic University, 2022)
The article provides an analysis of the state policy as an investor in the course of reforminghigher education system. Here the authors contemplate the problem of underutilization of resources of the network of national research universities by the state as a customer that decides on admission quotas for postgraduate education. The article provides an analysis of interaction between the state as an investor and customer and one specific national research university in the course of reforming higher education system. The article presents an organizational solution for optimization of university resources exploitation throughout the process of postgraduate education.